Towards intelligent manufacturing: equipping SOA-based architectures with advanced SLM services - Minguez, J.; Silcher, S.; Mitschang, B.; Westkamper, E. (НТУ "ХПИ", 2011)
The vision of knowledge-based and intelligent manufacturing systems is driving the development of system architectures, which can seamlessly manage information flows across multiple heterogeneous manufacturing systems and provide the necessary services to support the execution of production processes. Constantly changing business conditions and turbulent scenarios force manufacturing companies to continuously adapt their business processes and manufacturing systems. In such a context, a flexible infrastructure that supports the full integration of processes and adapts its services is needed. This paper presents an innovative semantic service framework that enables the adoption of service lifecycle management (SLM) in an SOAbased integration framework.

Предвосхищение основанных на знаниях и иcкусственном интеллекте производственных систем вызывает развитие системных структур, которые могут гибко управлять информационными потоками в параллелях совместно работающих производственных систем и обеспечивать необходимое обслуживание для поддержки выполнения производственных процессов. Постоянно изменяющаяся деловая конъюнктура и нестабильные сценарии действия производственных компаний побуждают их к постоянной готовности адаптировать производственные процессы и производственные системы к новым условиям. В таком контексте необходима гибкая инфраструктура, которая поддерживает полную интеграцию процессов и приспособлена к их обслуживанию. Статья представляет семантические основы инновационного подхода к обслуживанию, предоставляющего возможность адаптивного управления эксплуатационными ресурсами в интегрированных рамках обслуживающих структур.
Навстречу интеллектуальному производству SOA-базирующееся оборудование с современными системами SLM
Keywords: information; service-oriented architecture; service lifecycle management; framework; информация; обслуживающая структура